Census of Turin, Italy, 1705 - Balani, Donatella ([Verlag nicht ermittelbar], 2005)
This study is a census enumeration of the city of Turin, Italy, in 1705. The census was ordered by Duke Victor Amadeus II as the city prepared for a siege from part of the French army, as ordered by King Louis XIV. A house-by-house survey of all inhabitants was conducted to assess how many men were able to bear arms and how many people there were to feed. All of the inhabitants, including both citizens and immigrants streaming into the city from the surrounding countryside to escape the invaders, were listed by name, along with their ages, family relationships, birthplaces, occupations, dwelling places, and any weapons kept in the household. Fifty cantonieri (ward-captains) were assigned to survey the 122 isole (city blocks). The information for 15 of the isole are absent. This study also includes a WinZipped archive of AtlasGIS files, which can be used to produce maps of Turin, Italy.